Socio-Adaptive Thinking of Searching for an Architectural Connection to Improve the Lives of Students with Special Physical Needs as a Special Kind of Philosophical Communication - Hnat, Galyna; Babyak, Volodymyr; Hnes, Lyudmyla; Solovii, Liubov; Hnes, Ihor (Տիգրան Մեծ)
An analysis of the modern spiritual situation, particularly the Western world, prompts the idea that a person‟s place in it is becoming increasingly uncertain and contradictory. This is especially clear in various conflicts arising among people with disabilities because of infrastructure problems in educational insti-tutions. It is evident that disabled people and various categories of mentally and physically weakened people are a very significant part of our society, for which accessible and comfortable conditions of life and rehabilitation should be created. This requirement should be considered among the fundamental, and it should apply too many significant objects of the social infrastructure of modern cities, including their higher educational institutions. The primary purpose is to determine the ways of adapting the architectural environment of higher education institutions to the needs of persons with disabilities. The object of the research is the buildings and structures of higher education institutions. To achieve the goal of our research, we have used an IDEF0 model in achieving social adaptation and improving communication.
Keywords: Philosophical communication